Perceptions of Health Professions Students in the Implementation of Interprofessional Education in Disaster Simulation in Syiah Kuala University (International Journal of Education and Literature, 2025)
Indonesia’s high disaster risk needs health professionals equipped with strong interprofessional collaboration skills in disaster management. Interprofessional Education (IPE) through disaster response simulations is a strategic approach to enhance collaborative competencies among health sciences students. This study aims to explore health sciences students’ perceptions of IPE implementation during disaster response simulations at Syiah Kuala University and its impact on developing collaborative competencies. A qualitative descriptive design was employed. Participants included students from medical, nursing, psychology and dentistry study programs who participated in the disaster response simulation. Data were collected using in-depth interviews, and observation before, during and after the simulation. Findings revealed positive perceptions toward IPE implementation through simulation, which effectively improved understanding of professional roles, communication skills, team coordination, and disaster preparedness. Key facilitators included realistic scenarios, experienced facilitators, and reflective debriefing sessions. Challenges identified were differences in professional backgrounds, confusion in simulation role and limited simulation time. In conclusion, practical integration via disaster response simulation significantly enhances collaborative competencies among health sciences students.